Perkawinan Beda Agama di Tengah-Tengah Masyarakat Plural Berdasarkan Kajian Teks 1 Korintus 7:12-16 - Rusmanto, Ayub; Anastasia, Gracia; Angella, Shearen (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
Interfaith marriage in the midst of a plural society has become a major influence in the life of Indonesian society. Indonesian society which is plural with different values, traditions, cultures, beliefs and religions makes it possible for interfaith marriages to occur. This paper will describe interfaith marriages in the midst of a plural society by examining the text of 1 Corinthians 7:12-16. The research method used is a descriptive qualitative approach. Analyze and explain specifically the social events that occur in a plural society. The results of this study found out the opinions of Muslim, Christian, Catholic, Hindu, Buddhist and Confucian religious leaders regarding interfaith marriages. In addition, after learning about interfaith marriages, the researcher examines the text of 1 Corinthians 7:12-16 as a basis for Christian theology on how to react to it, as well as the relevance of the text of 1 Corinthians 7:12-16 for today's Christians.AbstrakPerkawinan beda agama di tengah-tengah masyarakat plural menjadi sebuah pengaruh besar dalam kehidupan masyarakat Indonesia. Masyarakat Indonesia yang plural dengan nilai, tradisi, budaya, keyakinan dan agama yang berbeda-beda mengakibatkan perkawinan beda agama dimungkinkan terjadi. Tulisan ini akan menguraikan perkawinan beda agama di tengah-tengah masyarakat plural menelisik teks 1 Korintus 7:12-16. Metode penelitian yang digunakan dengan pendekatan kualitatif deskriptif. Menganalisis dan menjelaskan secara spesifik peristiwa sosial yang terjadi di masyarakat plural. Hasil penelitian ini mengetahui pendapat para tokoh-tokoh agama Islam, Kristen, Katholik, Hindu, Budha dan Khonghucu tentang perkawinan beda agama. Selain itu, setelah mengetahui perkawinan beda agama, peneliti menelisik teks 1 Korintus 7:12-16 sabagai dasar teologi Kristen bagaimana menyikapinya , serta relevansinya teks 1 Korintus 7:12-16 bagi umat Kristen masa kini.